(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, Civil law reflects a system consisting of a number of legal institutions, property rights, obligation rights, personal non-property rights, rights based on the results of creative activity, inheritance rights. It is said that relations regulated by civil law constitute its subject.